2000
DOI: 10.1002/(sici)1096-8628(20000410)91:4<277::aid-ajmg7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

CFTR mutations in three Latin American countries

Abstract: We analyzed 192 cystic fibrosis (CF) alleles in three Latin American countries: Mexico, Colombia, and Venezuela. Mutation screening was performed by polymerase chain reaction (PCR) and a reverse dot blot detection kit that enables determination of 16 of the most common CF mutations worldwide. Mutations were detected in 47.9% of the screened CF alleles. The most prevalent CF allele was DeltaF508 (39. 6%). The remaining 16 non-DeltaF508 detectable mutations represented 8.3% of the CF alleles. Among them, the G54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…The frequency of this main mutation in Colombian CF patients is lower than the frequency in Northern European countries, USA and Canada, and similar to countries from Southern Europe (EWGCFC, 1990;Estivill et al, 1997), which apparently reflects the fact that the colonization of Colombia was mainly carried out by immigrants from Spain. Latin America's mean frequency (47.7%) (WHO Workshop 2002) is close to that from Colombia, but the range goes from 29% in Chile (Rios et al, 1994), 30% in Venezuela (Restrepo et al, 2000) and 34% in Cuba (Collazo et al, 1995), to 57% in Argentina (Chertkoff et al, 1997) and Uruguay (Luzardo et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of this main mutation in Colombian CF patients is lower than the frequency in Northern European countries, USA and Canada, and similar to countries from Southern Europe (EWGCFC, 1990;Estivill et al, 1997), which apparently reflects the fact that the colonization of Colombia was mainly carried out by immigrants from Spain. Latin America's mean frequency (47.7%) (WHO Workshop 2002) is close to that from Colombia, but the range goes from 29% in Chile (Rios et al, 1994), 30% in Venezuela (Restrepo et al, 2000) and 34% in Cuba (Collazo et al, 1995), to 57% in Argentina (Chertkoff et al, 1997) and Uruguay (Luzardo et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…probably reflects this contribution of African genes, since the patients from Ecuador (Guayaquil) [[37], Cassiman, personal communication] and Venezuela (Maracaibo)[34] come from regions with high admixture with Africans. Descendants of people from the Middle East are also numerous in these same regions, and thus could partly explain the distinct clustering.…”
mentioning
confidence: 99%
“…Northern Europeans are predisposed to unique diseases such as cystic fibrosis and idiopathic hemochromatosis. The respective Northern European alleles are found in other ethnic groups due to admixture [2729, 49–51]. The geographic distribution of the ΔF508 cystic fibrosis allele in Europe is similar to that of prostate cancer incidence, and the allele has been transmitted to African Americans and Latin Americans.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic epidemiology has shown that inter-group breeding leads to spreading of disease alleles among ethnic groups [2629]. In this sense, the geographic distribution of the varied frequencies reflects the migration, settlement, and admixture history of the susceptibility carrier.…”
Section: Analysesmentioning
confidence: 99%